Ghost in the H.A.T.B.O.X. - Beddor, Frank (Beddor, Frank. Hatter Madigan, 2016)
Cadet Hatter Madigan has entered Wonderland's Milinery Academy, where those born to protect queens will train to become assassins, bodyguards, and spies.